If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + -1) = 0 Reorder the terms: -1(-1 + x) = 0 (-1 * -1 + x * -1) = 0 (1 + -1x) = 0 Solving 1 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| (2)=2x-2 | | (0)=2x-2 | | (-2)=2x-2 | | -6z+1/3=6 | | 1/2+4x=3x+5/4 | | x+0.05x=31500 | | 3y=9(3)+3 | | 3y=9(2)+3 | | 3y=9(1)+3 | | 3y=9(0)+3 | | 3y=9(-1)+3 | | 6x+35=15x+4 | | 4h-k=x | | 12-15x=-2-15x | | y=-5(3)+5 | | y=-5(2)+5 | | y=-5(1)+5 | | y=-5(0)+5 | | 3x+7x-15=-2x+2x+25 | | x-6.1=8.97 | | y=-5(-1)+5 | | 3(2x+-1)=6x+5 | | 55=15+1/2D | | 24-8x^2-x^4=0 | | 3(2x+1)=6x+5 | | 9p+3=6+8p | | 3/7(1+6x)=1 | | 32-3x=20 | | 12x+1=2(6x+3) | | y=2(-1)+1 | | (1)-y=6 | | 3x+39=6x+13 |